OpusJava: A Java framework for distributed high performance computing - Laure, Erwin (Future generation computer systems, 2001)
The past few years have dramatically changed the view of high performance applications and computing. While traditionally such applications have been targeted towards dedicated parallel machines, we see the emerging trend of building “meta-applications” composed of several modules that exploit heterogeneous platforms and employ hybrid forms of parallelism. In particular, Java has been recognized as modern programming language for heterogeneous distributed computing. In this paper we present OpusJava, a Java based framework for distributed high performance computing (DHPC) that provides a high level component infrastructure and facilitates a seamless integration of high performance Opus (i.e., HPF) modules into larger distributed environments. OpusJava offers a comprehensive programming model that supports the exploitation of hybrid parallelism and provides high level coordination means.